2019
DOI: 10.1186/s40645-018-0244-z
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Quaternary record of marine organic carbon content in the hemipelagic sediments of the Japan Sea from bromine counts measured by XRF core scanner

Abstract: The marine organic carbon content in sediments is a useful tool for reconstructing past productivity in the ocean. Bromine has been proposed as a useful proxy for marine organic carbon, since bromine is more concentrated in marine organic matter compared to terrestrial organic matter. Here, we present a high-resolution Quaternary record of marine organic carbon in the hemipelagic sediments of the Japan Sea obtained during Integrated Ocean Drilling Program (IODP) Expedition 346. We measured the bromine content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…The b* color parameter, an indicator of diatom accumulation in sediments, Сa/Fe ratio, related to calcareous phytoplankton production, and chlorin content, responsible for chlorophyll production, are all proxies for surface water paleoproductivity in the NW Pacific and marginal seas (Nürnberg and Tiedemann, 2004;Riethdorf et al, 2013). Br concentration is an excellent indicator of the total organic content of sediment (Riethdorf et al, 2013;Seki et al, 2019). Based on variations in the productivity parameters in the Okhotsk and Bering Seas and in the ocean waters off Kamchatka, regional paleoproductivity of the studied areas increased during periods of climate warming and dropped during glacial periods (Nürnberg and Tiedemann, 2004;Gorbarenko et al, 2005;Riethdorf et al, 2013).…”
Section: Age Modelmentioning
confidence: 99%
“…The b* color parameter, an indicator of diatom accumulation in sediments, Сa/Fe ratio, related to calcareous phytoplankton production, and chlorin content, responsible for chlorophyll production, are all proxies for surface water paleoproductivity in the NW Pacific and marginal seas (Nürnberg and Tiedemann, 2004;Riethdorf et al, 2013). Br concentration is an excellent indicator of the total organic content of sediment (Riethdorf et al, 2013;Seki et al, 2019). Based on variations in the productivity parameters in the Okhotsk and Bering Seas and in the ocean waters off Kamchatka, regional paleoproductivity of the studied areas increased during periods of climate warming and dropped during glacial periods (Nürnberg and Tiedemann, 2004;Gorbarenko et al, 2005;Riethdorf et al, 2013).…”
Section: Age Modelmentioning
confidence: 99%
“…XRF scanning can measure many major and minor elements simultaneously while preserving the sediment intact (e.g., Croudace et al, 2006;Haschke, 2006;Haschke et al, 2002;Kido et al, 2006;Koshikawa et al, 2003;Richter et al, 2006;Wien et al, 2005). With measurements able to be acquired as close as every 100 μm of core, the near-continuous element records can then be related to past changes in Earth and ocean processes that affect the composition of the sediment (e.g., Hennekam et al, 2019;Peterson et al, 2000;Seki et al, 2019;Ziegler et al, 2013). Supporting Information:…”
Section: Introductionmentioning
confidence: 99%
“…The main sources of organic matter in marine sediments include the active pools of carbon in the oceans, atmosphere, landmasses and carbon pools that cycle on much longer, geological timescale (Pedrosa-Pàmies et al, 2015). However, in coastal marine sediments, organic matter is largely a mixture of terrestrial and marine organic matter and varies along coastal gradients with highest contents inshore than offshore (Krishna et al, 2013;Seki, Tada, Kurokawa, & Murayama, 2019). In this study, organic carbon content in sediments showed a gradual decrease along onshore-offshore gradient in the harbour channel containing clay-silt, sand and gravel sediments ( Figure 3) with medium content in sand-silt.…”
Section: Organic Carbon Distributionmentioning
confidence: 47%